2014
DOI: 10.1371/journal.pone.0103415
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Compound Heterozygous Mutations in MYO7A Associated with Usher Syndrome 1 in a Chinese Family

Abstract: Usher syndrome is an autosomal recessive disease characterized by sensorineural hearing loss, age-dependent retinitis pigmentosa (RP), and occasionally vestibular dysfunction. The most severe form is Usher syndrome type 1 (USH1). Mutations in the MYO7A gene are responsible for USH1 and account for 29–55% of USH1 cases. Here, we characterized a Chinese family (no. 7162) with USH1. Combining the targeted capture of 131 known deafness genes, next-generation sequencing, and bioinformatic analysis, we identified tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The details of the deafness gene capture, sequencing, and bioinformatics analysis methods have been described in detail previously [ 7 ]. According to the autosomal recessive pattern of inheritance, only variants that were homozygous or compound heterozygous in the affected siblings were selected as candidates.…”
Section: Methodsmentioning
confidence: 99%
“…The details of the deafness gene capture, sequencing, and bioinformatics analysis methods have been described in detail previously [ 7 ]. According to the autosomal recessive pattern of inheritance, only variants that were homozygous or compound heterozygous in the affected siblings were selected as candidates.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, molecular diagnosis through next-generation sequencing (NGS) has made it easier to diagnose deafness syndromes such as MTS, making diagnosis possible decades earlier, before all the phenotypes show. Targeted deafness genes combined with high-throughput sequencing can be regarded as a revolutionary technology with high speed and low cost to identify the pathogenic causes in a large number of syndromic hearing loss families [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical data to date indicate the NSHL phenotype in this family, the diagnosis of Usher syndrome cannot be totally excluded since MYO7A ‐related Usher syndrome usually presents with late‐onset retinal pigmented epithelium. The clinical features of Usher syndrome vary among and between families, especially with respect to the age of onset of eye disorder 30,39 . Further, one report suggested that DFNB2 and Usher syndrome patients may share the same mutations in MYO7A ‐mutated families 39 .…”
Section: Discussionmentioning
confidence: 99%